CO2 injection and storage in porous rocks: coupled geomechanical yielding below failure threshold and permeability evolution. Issue 1 (2022) - Tsopela, Alexandra; Bere, Adam; Dutko, Martin; Kato, Jun; Niranjan, S. C.; Jennette, Benjamin G.; Hsu, Sheng-Yuan; Dasari, Ganeswara R.
No abstract available